Validation of Doppler Temperature Coefficients and Assembly Power Distribution for the Lattice Code KYLIN V2.0. - Jichong, Lei; Jinsen, Xie; Zhenping, Chen; Tao, Yu; Chao, Yang; Bin, Zhang; Chen, Zhao; Xiangyang, Li; Jiebo, Wu; Huajian, Zhang; Nianbiao, Deng (Frontiers in Energy Research, 2021)
In this paper, we use the Doppler coefficient numerical benchmark problem proposed by Los Alamos National Laboratory and the power distribution of AFA-3G fuel assemblies at different burnup depths to verify and analyze the advanced neutronic assembly program KYLIN V2.0 developed by the China Institute of Nuclear Power. The analysis results show that the Doppler coefficients calculated by KYLIN V2.0 are in good agreement with the results of other well-known software in the world, and the power distributions of AFA-3G fuel assemblies at different burnup depths are in good agreement with the results of RMC calculations, and the error distribution is in accordance with the normal distribution; this shows that KYLIN V2.0 has high calculation accuracy and meets the core design requirements. It shows that KYLIN V2.0 has high calculation accuracy and meets the engineering design requirements.